Komparasi Kinerja Pertumbuhan Ikan Nila (Oreochromis niloticus) pada Sistem Resirkulasi dengan Media Filter yang Berbeda - Ni Nyoman Dian Martini (Jurnal Pendidikan Biologi Undiksha, 2024)
The quality of water as a maintenance medium in the recirculation system can decrease rapidly due to feeding activitiescarried out by fish such as waste in the form of faeces and leftover feed that settles to the bottom of the water. Water treatmentand optimization of filter media are ways to reduce pollutants dissolved in water. The purpose of this study was to determinethe survival rate and growth rate of tilapia (Oreochromis niloticus) reared in a recirculation system with different filter media.There were 3 (three) filter media treatments in wastewater treatment with recirculation systems, namely P0 filter mediawithout pakcoy plants, P1 filter media with pakcoy plants and P2 filter media with pakcoy plants and additional pumice.Evaluation of survival and growth of fish using oneway Anova data analysis. The results of the study during the 30-day rearingperiod showed that the highest survival value and growth rate of fish were obtained in the treatment of filter media withpakcoy plants and additional pumice. During the research, treatment P0, P1, and P2 respectively gave fish survival rates of78.2%, 80.2% and 85.0%, absolute weight gain of 10.12 g, 12.09 g and 15.19 g and the absolute length of 2.46 cm, 3.21 cmand 4.81 cm. The survival rate of tilapia (O. niloticus) in three different recirculation systems did not show a significant effect(P > 0.05) but had a significant effect (P < 0.05) on growth. The result of the study showed that tilapias from the recirculatingsystem with pakcoy plants and additional pumice as filter media provides better growth performance compared to the systemwithout pakcoy plants and additional pumice via improved water quality throughout the culture.